Activity of Synthetic Phospholipids in Blood Coagulation - Daemen, F. J. M; van Arkel, C; Hart, H Ch.; van der Drift, C; van Deenen, L. L. M (Thrombosis and Haemostasis, 1965)
1. An investigation was made into the activity of synthetic phospholipids on blood coagulation in vitro, utilizing synthetic substances including phosphatidyl ethanolamine and phosphatidyl serine containing a poly-unsaturated fatty acid constituent.2. Applying a one-stage recalcification test, phosphatidyl serine was found to act at high concentrations as anticoagulant. No clot-promoting activity was observed after addition of individual phospholipids. However, several combinations of phospholipids, e.g. phosphatidyl ethanolamine with phosphatidyl serine or certain mixtures of lecithin with phosphatidylserine, shortened the clotting time.3. In the thromboplastin generation test phosphatidyl ethanolamine exhibited some acceleratory activity without being able, however, to replace crude brain cephalin completely. However, optimal coagulant activity was produced by mixtures of synthetic phospholipids viz, phosphatidyl ethanolamine with phosphatidyl serine, phosphatidic acid or (isolated) cardiolipin and by certain combinations of lecithin and phosphatidyl serine.4. In both assay systems the maximum activity of each phospholipid combination was found to be related within certain limits to the ratio of both compounds. It is concluded that the coagulant activity of phospholipids in vitro is not to be attributed to a certain type of phospholipid or a defined mixture. The results obtained with the synthetic compounds appear to support the view that a particular negative surface charge of the phospholipid micelles is a prerequisite for maximal clot-promoting activity of phospholipids.